How I See and Feel About Myself: Domain-Specific Self-Concept and Self-Esteem in Autistic Adults - Nguyen, William; Ownsworth, Tamara; Nicol, Chelsea; Zimmerman, David (Frontiers in Psychology, 2020)
Few studies have examined the self-perceptions of autistic adults. This study aimed firstly to investigate domain-specific self-concepts and global self-esteem in autistic adults. The second aim was to examine associations between autism self-appraisals, perceived social support and global self-concept and self-esteem. The third was to determine which domains of self-concept were most closely associated with self-esteem. Participants included 71 autistic adults aged 18-70 years and 65 age, sex and education matched typically developing individuals. Participants completed an online survey of autism characteristics, global self-esteem and domain-specific self-concepts (i.e., likeability, task accomplishment, power, giftedness, invulnerability & morality), self-appraisals about autism, and perceived social support. Autistic participants reported significantly lower power and global self-esteem than typically developing individuals after controlling for autism characteristics. More positive self-appraisals about autism (i.e., greater perceived benefits and lower helplessness) were significantly related to better global self-concept and self-esteem. Global self-esteem was significantly and positively associated with perceptions of giftedness, emotional resilience and power. These findings suggest that autistic adults may perceive themselves as having a low sense of power in their relationships and have negative global perceptions of their self-worth. However, those able to find positive meaning or benefits associated with autism are likely to have more positive global self-perceptions. This study provides new insights into how autistic adults perceive themselves which may guide the focus of psychosocial interventions that seek to recognise and promote unique talents and emotional resilience.